Caritas Pirckheimer : a journal of the Reformation years, 1524-1528 - Pirkheimer, Charitas, 1466 or 1467-1532 (Library of medieval women., 2006)
Caritas Pirckheimer was the abbess of St Clare's in Nürnberg. Her Journal depicts her struggle against the city council's attempts to reform and close her nunnery.